The Participation of the People in Formulating the Strategic Plan Policy in Udon Thani Province - Sittivongsa, Boonpeng (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objective of research article were to 1) study the participation of the people in the formulation of the Udon Thani strategic plan and 2) study the development guidelines for public participation in the formulation of the Udon Thani strategic plan. The researcher used a blended research model. Using quantitative research which is a survey research and qualitative research methods using in-depth interviews. From key contributors by collecting information from relevant documents and research the tools used to collect the data were questionnaires for quantitative research. And interview form Used for qualitative research the sample group used to answer the questionnaire totaled 400 people and target groups of 12 interviewed people. The data analysis was used statistical distribution of frequency, percentage, mean and standard deviation and using descriptive data analysis. The research results were found that: 1. The level of participation in the determination of the overall provincial strategic plan in all aspects, the variables according to the 3 aspects were found to be at the medium level. 2. Development guidelines for public participation in the formulation of the Udon Thani strategic plan participation in provincial strategic planning should prepare for the formulation of strategic plans and public relations. Participation in implementing the provincial strategic plan People should be involved in the preparation of the project. Establish objectives, goals, activities in implementing the provincial strategic plan, knowing about integrating the people's needs database. To support the implementation of the provincial development supervision plan continuously. Participation in the assessment of the provincial strategic plan government agencies should evaluate their participation in the formulation of strategic plans and implement them in improvement and development, have a system and assess the implementation of all stages of access to services for people in a concrete campaign.